2014
DOI: 10.1016/j.trpro.2014.10.093
|View full text |Cite
|
Sign up to set email alerts
|

Driver Behavior Characterization in Roundabout Crossings

Abstract: Roundabouts are widely accepted for their safety, capacity and environmental advantages. Although it can be easily recognized that the driver behavior is mostly related with the roundabout geometry. This paper presents a detailed characterization of the driver behavior while crossing three consecutive double-lane roundabouts in an arterial road. Driver behavior was described in three main levels: i) speed profiles; ii) lateral acceleration profiles; iii) roundabout geometry. It is shown that roundabouts can su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Therefore, alternative methods used video detection or image processing to obtain complete speed profiles (50)(51)(52). Other studies used speed data collected by car-following (21,53) or by instrumented vehicles (54).…”
Section: Analysis 2-speedmentioning
confidence: 99%
“…Therefore, alternative methods used video detection or image processing to obtain complete speed profiles (50)(51)(52). Other studies used speed data collected by car-following (21,53) or by instrumented vehicles (54).…”
Section: Analysis 2-speedmentioning
confidence: 99%
“…The study site had a posted speed limit of 31.25 mi/h (50 km/h) and was located in an urban environment. The researchers found that the total influence area of the roundabout, which includes the upstream influence area, the downstream influence area, and the width of the roundabout, was between 1300 ft and 1640 ft (400 and 500 meters), with the width/diameter of roundabouts ranging from 185 ft to 210 ft (55 m to 64 m) (8). An older study by Violette and Cardon (1992) suggested that the total length of the influence zone of a roundabout including upstream, downstream, and width of the roundabout can be between 600 m and 1000 m (1900 ft and 3280 ft).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The second subgroup, roundabout behaviour, contains articles that aim to analyze driver behaviour solely at roundabout locations. Statistical analysis and evaluation of driver's behaviour when crossing roundabouts is presented in detail in Silva et al (2014). Also, Zyner, Worrall & Nebot (2019) presented a method for predicting driver intention at roundabouts through the use of recurrent neural networks combined with a mixture density network output function.…”
Section: Specific Location Behaviourmentioning
confidence: 99%
“…Researchers need to pursue this domain, to better understand the human factors that contribute to crashes, with the hopes of reducing future traffic accidents and improving pedestrians' and passengers' well-being, because drivers' behaviour has a strong impact on traffic safety (Silva & Eugenio Naranjo, 2020). Moreover, analyzing specific behaviours, such as car-following, or analyzing drivers' behaviour concerning specific geometric locations, such as intersections, would help understand how certain behaviours contribute more than others to crashes, and why crashes occur more often on particular locations Gadepally, Krishnamurthy & Ozguner (2013) and Silva et al (2014). Also, identifying different driving styles and patterns would help make tailored policies and regulations for drivers of certain ages and driving experiences, and guidelines for correcting dangerous behaviours.…”
Section: Benefits Of Improving Traffic Safetymentioning
confidence: 99%